Genome-wide identification and characterization of circular RNAs for exogenous trehalose-mediated heat stress responses in tea plants (Camellia sinensis) - Zheng, Shizhong; Liu, Chufei; Zhou, Ziwei; Xu, Liyi; Ruan, Biyuan; Chen, Xiaohui (Frontiers in Plant Science, 2024)
Background Heat stress is one of the main environmental factors limiting the growth, yield and quality of tea plants (Camellia sinensis). Trehalose involved in plant responses to multiple adverse environmental stresses, including heat stress. However, the roles of circular RNAs (circRNAs) and their involvement in the trehalose response to heat stress remain unknown. Methods In this study, circRNA-sequencing was performed to analyze the characteristics of circRNAs in trehalose-induced responses to heat stress in tea plants. Kyoto Encyclopedia of Genes and Genomes enrichment analysis was used to determine the potential function of circRNAs, and the expression of differentially expressed circRNAs (DECs) and their host genes related to Non-homologous end-joining (NHEJ) and Homologous recombination (HR) were analyzed. To further explore the effect of trehalose on DNA double strand breaks (DSBs), the reactive oxygen species (ROS) contents, specially hydrogen peroxide (H2O2) and superoxide anion (O2−), in heat-stressed tea plants were investigated. Results A total of 11402 circRNAs were detected from CK, T (heat stress) and TT (heat stress + trehalose) samples. Among these circRNAs, 573, 620 and 550 circRNAs were identified as differentially expressed in the T vs. CK, TT vs. CK and TT vs. T comparison groups, respectively. The host genes of DECs were enriched in NHEJ and HR pathways, implying a critical role of circRNAs in DSBs repair. The expression level of circKu70-1 and circKu70-3 showed positive correlations with their host gene, ATP-dependent DNA helicase II 70 kDa subunit (CsKu70), while circKu70-2 exhibited an opposite expression trend. Similarly, circRad50 displayed a negative correlation with its host gene, DNA repair protein RAD50 (CsRad50). Notably, the expression of CsKu70 and CsRad50, which are crucial for initiating DSB repair, was decreased in the trehalose-treated (TT) samples. This finding suggests that trehalose may play a role in modulating the expression of circRNAs and their host genes involved in NHEJ and HR pathways, ultimately contributing to reduced DSB damage during heat stress. Moreover, exogenous trehalose significantly reduced H2O2 and O2− contents in tea plants under heat stress, suggesting that trehalose could mitigate heat-induced damage resulting from ROS overproduction. Conclusion Our results indicated that circRNAs play a crucial role in maintaining genome integrity. Specifically, they may function as molecular hubs that respond to changes of the levels of H2O2 and O2− induced by trehalose, and subsequently regulate the DSBs mediated by their host genes. This, in turn, further impacts genome stability, ultimately enhancing heat tolerance in tea plants. Our findings provided new insight into the potential applications of trehalose as an agrochemical in tea plants and revealed the potential role of circRNAs in tea plants heat tolerance.